THE INFLUENCE OF TASTE AND PRICE ON PURCHASE DECISIONS CASE STUDY OF NOMO COFFEE SHOP IN BANDUNG - Muhamad Irvan; Agis Maharani; Muhammad Nizar Dzaki (Journal of Business Administration, 2022)
The development of the coffee industry in Indonesia has increased rapidly in recent years. In the face of increasingly fierce competition, coffee shops have become one of the favorite places for people to enjoy coffee. One of the famous coffee shops in Bandung is "Nomo Coffee". Currently, "Nomo Coffee" faces challenges in maintaining and increasing the number of customers amid increasingly fierce competition. The purpose of this study was to analyze the influence of taste and price on consumer purchasing decisions at "Nomo Coffee" in Bandung. The method that will be used in this study is a structured survey that will be run through a questionnaire to consumers "Nomo Coffee". The results of the descriptive analysis showed that most respondents gave a low to moderate rating on the taste of products at Nomo Coffee. This analysis provides an initial picture of consumer perceptions of the taste and price of products at Nomo Coffee. Furthermore, further analysis such as regression analysis can be performed to determine the extent to which taste and price influence on consumer purchasing decisions. Regression analysis shows that the variable "Taste" has a regression coefficient of 0.589, with a t-value of 3.725 and a significance of 0.001. Meanwhile, regression analysis shows that the variable "Price" has a regression coefficient of 0.378, with a t-value of 2.198 and a significance of 0.035. The results showed that the taste of the product has a strong influence on consumer purchasing decisions at Nomo Coffee. The importance of efforts to improve the quality of coffee taste and maintain competitive prices to influence consumer purchasing decisions in coffee shops. Coffee shop "Nomo Coffee" can focus on improving coffee quality, such as through the selection of high-quality coffee beans and good brewing techniques.